2022
DOI: 10.3390/nu14163360
|View full text |Cite
|
Sign up to set email alerts
|

Trans Fatty Acids Content in Whole-Day Diets Intended for Pregnant and Breastfeeding Women in Gynaecological and Obstetric Wards: Findings from the Study under the “Mum’s Diet” Pilot Program in Poland

Abstract: Trans fatty acids (TFAs) have been proven to have an adverse effect on human health by interfering with n-3 long-chain polyunsaturated fatty acids (n-3 LC-PUFA) synthesis. LC-PUFA n-3 are necessary for the development and maturation of the nervous system and retina during the prenatal period and infancy. TFAs are not synthesized de novo in the human body. Their presence in body fluids arises from the diet. The aim of our study was to determine the content of TFAs in individual meals and in a whole-day hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Table 2 summarizes the total TFA values of various food groups based on recent measurements in Thailand ( 77 ), Egypt ( 78 ), Argentina ( 75 ), Spain ( 74 ), Jamaica ( 79 ) and Malaysia ( 80 ). Previous research has shown that both voluntary and regulatory measures to reduce iTFA content in foods have resulted in substantial reductions in global intakes of TFAs over the past two decades ( 61 , 81 , 82 ), including Canada ( 83 ) and the European Union (EU) countries ( 84 ). The estimated intake of TFAs in 2010 varied widely from 0.2 E% (Barbados) to 6.5 E% (Egypt) ( 82 ), while seven years later, intake was lower, ranging from 0.3 E% (China) to 4.2 E% (Iran).…”
Section: Fatty Acids In Generalmentioning
confidence: 99%
“…Table 2 summarizes the total TFA values of various food groups based on recent measurements in Thailand ( 77 ), Egypt ( 78 ), Argentina ( 75 ), Spain ( 74 ), Jamaica ( 79 ) and Malaysia ( 80 ). Previous research has shown that both voluntary and regulatory measures to reduce iTFA content in foods have resulted in substantial reductions in global intakes of TFAs over the past two decades ( 61 , 81 , 82 ), including Canada ( 83 ) and the European Union (EU) countries ( 84 ). The estimated intake of TFAs in 2010 varied widely from 0.2 E% (Barbados) to 6.5 E% (Egypt) ( 82 ), while seven years later, intake was lower, ranging from 0.3 E% (China) to 4.2 E% (Iran).…”
Section: Fatty Acids In Generalmentioning
confidence: 99%